Evaluación de registros de cementación a través de la automatización con aprendizaje de máquinas en pozos de la Orinoquia colombiana. (2023)
In this research, a tool is developed that facilitates both the veracity of the cementation record and its interpretation, using different digital applications, such as Python and C#, implementing principles such as descriptive statistics, Big Data and Deep learning. In order to generate an interpretation of the record through image analysis, with neural networks, covering the bias that exists at the time of interpreting the record, given that this interpretation is carried out manually and by an expert on the subject. . For this reason, we first seek to parameterize variables such as transit time, eccentricity and tension as factors that indicate the quality of the record at the time of its run.